The opportunity for and intensity of sexual selection in a seed bug depend on host plant dispersion. Issue 2 (4th March 2023) - McLain, Denson K.; Pratt, Ann E.
Abstract : In fields of the coastal plain of Georgia (USA), the seed bug, Neacoryphus bicrucis, feeds and mates exclusively on ragwort. The distribution of ragwort, Senecio tomentosus, is either dispersed, with small numbers of plants spread over large areas, or clustered, with large numbers of plants concentrated into relatively small areas. In dispersed habitat, the density of seed bugs is always low (< 20/0.25 m 2 ) as is the proportion of adults who are mating (20%). In clustered habitat, adult densities are occasionally high (30–75/0.25 m 2 ) as are mating rates (> 67%). In both habitats, mating males are in better condition (= mass – mass expected from length) than non-mating males. In clustered habitats, aggression between males occurs frequently and determines residency in areas of high ragwort abundance to which females are especially attracted for mating and oviposition. A mark-recapture study revealed that males move about more in dispersed than clustered habitats, possibly searching for mates. Variance in male mating efficiency (copulations/sightings) matches random expectations in dispersed habitats but is significantly higher than that in clustered habitats, suggesting greater opportunity for sexual selection. A multivariate analysis of selection intensity using mark-recapture data revealed that longer wings and shorter bodies are favored in dispersed habitat, suggesting selection on ability to search for mates. In clustered habitat, selection favors a longer body, antennae, and legs. This finding suggests selection favoring dominance in aggressive interactions, as legs and antennae are used to grapple with opponents and to seize females during aggressive courtship.